Dinâmica populacional de Rhipicephalus (Boophilus) microplus (Canestrini, 1887) em bovinos mestiços mantidos em pastagens de Brachiaria decumbens no município de Formiga, Minas Gerais - Gomes, Lucas Vinícius Costa [UNESP] (2015)
Considering the great importance of Rhipicephalus (Boophilus) microplus in cattle, the present study aimed to evaluate the seasonality of this arthropod in cattle maintained in pastures of Brachiaria decumbens. To that end, were investigated the population dynamics for 12 months in the city of Formiga, Minas Gerais. Twenty-four cattle with eight to 12 months of age were subjected to natural infestation by ticks. Counts of partially engorged females, from 4,5 to 8,0 mm (engorged), were computed on the left side of each animal, at times -2, -1 and zero. Using the mean on those dates tick counts, randomization was executed, to obtain two groups with fair infestations, which were kept in separate paddocks. To study of seasonality, the counts were recorded at 3, 7, 14, 21, 28, and every 14 days for 12 months. To check the ectoparasitic incidence with the climatic effects, were collected from the climatological station of the city, the following data: maximum and minimum temperature, rainfall and relative humidity. Tactical treatments were performed, topically (spray) with a formulation containing Cypermethrin 15 % + Chlorpyrifos 25% + Piperonyl butoxide 15 + Citronella 1% on all the dates on which tick measurements exceed 30 engorged on average. As an adjunct to the project, were also carried weights of animals and faeces samples for egg counts per gram of feces (EPG) every 28 days, and they are treated with injectable Levamisole Phosphate at a dose of 4,7 mg/kg, reaching average of EPG ≥ 300. The mean parasite load per animal and group I standard deviation was 18,7 (± 11,7) and group II 25,9 (± 22,6) and were performed 15 acaricide treatments in both groups. The EPG counts were more elevated in the months of December and May, and made two treatments in each group, a total of four anthelmintic treatments throughout the study. There was no statistical difference between the mean weight of the two analyzed groups (p>0,05), as well ...